Refleksi Hukum atas Pelaksanaan Pasal 231 KUHAP: Upaya Realisasi Perlindungan Hak Korban Tabrak Lari di Polresta Gorontalo Kota - Rosela Ismail Musa; Suwitno Yutye Imran; Karlin Z. Mamu (Yayasan pendidikan dzurriyatul Quran, 2026)
This study aims to analyze the implementation of Article 231 of the Indonesian Criminal Procedure Code (KUHAP) as a legal basis for protecting the rights of victims in hit-and-run crimes within the jurisdiction of the Gorontalo City Police (Polresta Gorontalo Kota). Normatively, Article 231 KUHAP grants victims or their heirs the right to file a compensation claim integrated into the criminal case process; however, its practical enforcement faces various obstacles. This research employs an empirical legal method using a juridical-sociological approach by examining the implementation of the legal provisions through interviews with law enforcement officers and crime victims, as well as analysis of primary and secondary legal sources. The findings indicate that the enforcement of Article 231 KUHAP in Gorontalo City is not yet optimal due to juridical, structural, and cultural constraints. These include the absence of clear technical guidelines, limited human resources and inter-institutional coordination, and the low legal awareness among victims and the public. To optimize victim protection, the study recommends strengthening legal socialization, enhancing law enforcement capacity, building coordination with the Witness and Victim Protection Agency (LPSK), and applying restorative justice principles as an alternative approach. Therefore, the implementation of Article 231 KUHAP should be directed toward a criminal justice system oriented to comprehensive and humane victim recovery.